Infrared thermography as a non-invasive method for evaluating stress in lactating dairy cows during isolation challenges - Mincu, Madalina; Nicolae, Ioana; Gavojdian, Dinu (Frontiers in Veterinary Science, 2023)
The overall objective of the current data report was to evaluate and test the feasibility of using infrared thermography (IRT) as a non-invasive method for measuring stress signs in lactating dairy cows during short negative challenges, such as visual isolation from herd-mates. The study was carried out at the Experimental Farm of the Research and Development Institute for Bovine Romania, on 20 Holstein-Friesian lactating multiparous dairy cows, between August and September 2022. Cows were housed in two identical tied stanchion barns (170/85 cm), and were isolated individually from the herd for 240 min. post-morning milking. Our results shown significant (p≤0.05) rises for both orbital and nasal IRT temperatures following the isolation challenge, suggesting that such approaches could represent adequate tools for assessing social stress in cattle. Overall, current results are in accordance with previous studies which validated both eye and nasal regions as IRT thermal windows for studying the effects of painful and negative contexts on stress response in farmed ruminants, while considering the stress-induced hyperthermia as an integral part of the physiological response to negative stimuli, as well as the current limitations that this tool faces.